Pengaruh Pemahaman Konsep Asemen HOTS terhadap Kemampuan Guru Matematika SMA/SMK Menyusun Soal HOTS - I Wayan Widana (Emasains : Jurnal Edukasi Matematika dan Sains, 2020)
The ability of SMA/SMK mathematics teachers to develop HOTS-based Assessment is one of the important competencies in the Industrial Revolution 4.0. However, the field facts show that the ability of teachers to develop HOTS-based Assessment is very low, thus impacting on the low ability of students to solve contextual problems. This study aims to determine the direct effect of the teacher's understanding of the HOTS concept and the teacher's ability to develop HOTS-based Assessment. The study was conducted using a survey method, with a population of SMA/SMK mathematics teachers in the provinces of Bali, NTB, and NTT. The total sample of 400 people, selected using multistage random sampling techniques. The data were collected by questionnaire and analyzed by linear regression using SPPSS 23.0. The analysis showed that the teacher's understanding of the HOTS concept had a direct positive effect on the ability of the teacher to develop HOTS-based Assessment, with a value of F=521.291 (sig.=0.000) and a value of R-Square=0.567 which meant that the understanding of SMA/SMK mathematics teacher about the HOTS concept contributed 56.7% to the ability of SMA/SMK mathematics teachers to develop HOTS-based Assessment, while 43.3% was influenced by other factors.